Numerical Method of Studying the Focused Field of Matrix Acoustic Emitters - Sergii, Kozeruk (Fundamental Research and Application of Physical Science Vol. 3, 2023)
Focused acoustic beamforming for high resolution and signal-to-noise ratio in the space domain is relevant for location applications. Analysis of the acoustic field created by an emitter of complex geometry is a difficult diffraction task. Rayleigh's integral provides a fundamental opportunity to calculate the potential of the emitter field at each point in space. The purpose of the work is to create a mathematical apparatus for calculating the focused acoustic field of matrix emitters. A numerical approach to solving the Rayleigh integral is applied to the emitter, which is an array of sources with a short wavelength. The radiation pressure in the focal region is estimated as the sum of the contributions of individual discrete sources taking into account their focusing. The axial and radial distribution of pressure in the focal region for disc and square emitters was analyzed. The dependence of the length and width of the focal region on the size of the aperture of the disk emitter was obtained.